A Tiered Geospatial Sensing Framework for Context-Aware Content Delivery: Application in Scriptural Information Systems - Bagas Imanuel Pasaribu; Yudhy Setyo Purwanto (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2026)
Background: Current digital Bible applications predominantly utilize "pull-based" interactions, which fail to synchronize content delivery with the user’s immediate physical environment or situational context. Objective: The purpose of this research is to develop and evaluate a "push-based" framework that leverages tiered geospatial sensing to deliver contextually relevant scriptural content automatically without human intervention. Methods: Adopting an engineering-focused system design, the study integrated an OS-level Geofencing API with a custom 180-second dwell-time algorithm to filter transient noise, including high-speed movement (e.g., driving) and GPS jitter. The architecture was validated through twenty simulated field trials across diverse urban and suburban environments, specifically measuring trigger accuracy and battery efficiency. Results: The system achieved an 83.3% success rate for intended events, with the dwell-time filter successfully suppressing erroneous triggers during transient movement. Technical logs demonstrated a 67% reduction in battery consumption compared to continuous GPS polling. However, signal attenuation was identified as a significant limiting factor in high-density medical facilities and "urban canyon" environments. Conclusion: The results indicate that a tiered sensing model provides a reliable, energy-efficient solution for context-aware content delivery. By documenting the relationship between architectural density and signal deviation, this study establishes a technical blueprint for the intersection of geospatial informatics and digital theology. Future research should focus on refining multi-path mitigation techniques to improve reliability in dense structural environments.